Lateral parabrachial nucleus astrocytes control food intake - Mishra, Devesh; Richard, Jennifer E.; Maric, Ivana; Shevchouk, Olesya T.; Börchers, Stina; Eerola, Kim; Krieger, Jean-Philippe; Skibicka, Karolina P. (Frontiers in Endocrinology, 2024)
Food intake behavior is under the tight control of the central nervous system. Most studies to date focus on the contribution of neurons to this behavior. However, although previously overlooked, astrocytes have recently been implicated to play a key role in feeding control.Most of the recent literature has focused on astrocytic contribution in the hypothalamus or the dorsal vagal complex. Contribution of astrocytes located in the lateral parabrachial nucleus (lPBN) to feeding behavior control remains poorly understood. Thus, here we first investigated whether activation of lPBN astrocytes affects feeding behavior in male and female rats using chemogenetic activation. Astrocytic activation in the lPBN led to profound anorexia in both sexes under both ad libitum feeding schedule as well as after a fasting challenge. Astrocytes have a key contribution to glutamate homeostasis and can themselves release glutamate. Moreover, lPBN glutamate signaling is a key contributor to the potent anorexia which can be induced by lPBN activation. Thus, here we determined whether glutamate signaling is necessary for lPBN astrocyte activation induced anorexia, and found that pharmacological N-methyl D-aspartate (NMDA) receptor blockade attenuated the food intake reduction resulting from lPBN astrocyte activation. Since astrocytes have been shown to contribute to feeding control by modulating the feeding effect of peripheral feeding signals, we further investigated whether lPBN astrocyte activation is capable of modulating the anorexic effect of the gut/brain hormone -glucagon-like peptide-1 (GLP-1) as well as the orexigenic effect of the stomach-produced hormone -ghrelin, and found that the feeding effect of both signals are modulated by lPBN astrocytic activation. Lastly, we found that lPBN astrocyte activation induced anorexia is affected by diet-induced obesity challenge, in a sex divergent manner. Collectively, current findings uncover a novel role for lPBN astrocytes in feeding behavior control.